Portraying Dr. Soetomo's Thoughts in The Frame of University Social Responsibility - Nurhayati; Irianto, Gugus; Rosidi (Accounting Department, 2023)
Purpose - This research aims to understand and explain the concept of University Social Responsibility by Dr. Soetomo University Surabaya. Design/methodology/approach - In the context of research on University Social Responsibilities (USR), it is based on the concept of nationality and peoplehood initiated by Dr. Soetomo. Such a paradigm in the research context is called a constructivist-interpretive paradigm with a qualitative approach. A qualitative approach was chosen to obtain an in-depth picture of the research topic based on qualitative data. Findings - The findings in this study are as follows: First, the concept of University Social Responsibility implemented by Dr. Soetomo University Surabaya is understood as a forum for embodying values that have grown and developed within Dr. Soetomo University. Second, implementing University Social Responsibility based on a people's and national perspective at Dr Soetomo University Surabaya is a series of field practice agendas that students assisting residents measurably and simultaneously carry out. Third, the strategy carried out by Dr. Soetomo University Surabaya in implementing University Social Responsibility for the campus circle community is first to identify the fundamental problems that exist in the community, then consolidate empowerment together with the government, both the Surabaya City Government and the Surabaya city social service. The suggestions resulting from this study are: First, policies related to poverty alleviation, public education, equitable distribution of education, and education for all those driven by the city/district government and the House of Representatives should have synergy with universities or universities that also have similar views on efforts to alleviate poverty and equalize social access. Second, the Surabaya City Government and social services are advised to contribute financially and non-financially to the sustainability of the agenda related to equitable access in the context of fulfilling the fundamental rights of the need for human rights contained in Law Number 39 of 1999 concerning human rights.